Analisis Pengaruh Variasi Material Substitusi Terhadap Koefisien Permeabilitas pada Timbunan Tanah Lanau Berlempung - Era Agita Kabdiyono; Alizar Alizar; Okinawa Surya Putra Pratama (Jurnal Multidisiplin Indonesia, 2026)
Clayey silt is a soil type commonly found in Indonesia; however, it often causes problems in embankment construction due to its low permeability. This characteristic restricts water flow, leading to prolonged waterlogging and potentially reducing the stability of road and drainage infrastructure. This study aims to analyze the effect of adding substitute materials on improving the coefficient of permeability (k) of clayey silt and to determine the optimum mixture composition. The research method used was a laboratory experimental approach, including testing the physical properties of the original soil, such as specific gravity, Atterberg limits, and sieve analysis. Standard Proctor compaction testing was conducted to determine the optimum moisture content and maximum dry density, while permeability testing was carried out using the falling head method. The mixture variations consisted of substitute materials, such as sand or stone ash, added at percentages of 0%, 10%, 30%, 50%, and 70% based on the dry weight of the soil. The expected result of this study is the identification of the relationship between the percentage of substitute material and changes in permeability values. Therefore, this research is expected to provide technical recommendations for effective, economical, and applicable embankment soil improvement to mitigate the risk of waterlogging.